Adnexal mass: a clinicopathological study at a tertiary care centre in Assam, India - Das, Mukut Jyoti; Phukan, Pranay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: An adnexal mass may be found in females of all ages with significantly variable prevalence, but more common among women of reproductive age. Adnexal masses pose a special dilemma to the attending gynaecologist because the diagnosis is often difficult and differential diagnosis is vast. Clinical examination is the first step in evaluation of patients with adnexal mass. Pelvic masses which are undetected or overlooked on physical examination can be identified by Ultrasonography. The aims and objectives of the study were to: to find out different types of adnexal pathology clinically, correlation of clinical finding with histopathology, correlation of ultrasonography finding with histopathology. Methods: The present study was carried in the Department of Obstetrics and Gynecology, Assam medical college and hospital, Dibrugarh from 1st July 2017 to 30th June 2018. This study was a hospital based observational study which included 145 patients of adnexal mass attending the GOPD who required admission and operative intervention. All cases underwent an abdominal ultrasound examination with color Doppler. Transvaginal sonography was done wherever feasible. Following surgery, specimens were sent for histopathological examination and the reports were correlated with pre-operative clinical and ultrasonography findings. Results: The most common site of origin of adnexal mass was ovary (92.41%) followed by fallopian tube (6.20%) and broad ligament (1.39%). Majority (79.31%) were non neoplastic or benign adnexal masses. All cases of adnexal malignancy were of ovarian origin. The sensitivity and specificity of clinical examination for diagnosis and discriminating benign and malignant ovarian neoplasms were 70% and 86.6% and that of ultrasonography was 86.67% and 96.65% respectively. Conclusions: Adnexal mass in reproductive age group were mostly non neoplastic and benign, whereas malignancy was mostly seen in peri and post-menopausal age group. Ultrasonography is a useful adjunct to clinical examination for diagnosis and proper management of patients with adnexal mass in low resource setup.